Understanding stigma and suicidality among gay men living with HIV: A photovoice project - Olivier Ferlatte; Ingrid Handlovsky; Damien Ridge; Tara Chanady; Rod Knight; John L. Oliffe (Elsevier, 2022)
Gay men living with HIV (GMHIV) are at relatively high risk for suicide. To inform tailored suicide prevention interventions, we conducted a photovoice study with 22 GMHIV with a history of suicidality. Our study findings revealed three discrete but connected themes characterizing suicidality among GMHIV: first, HIV stigma featured prominently in participants' narratives who described accumulating experiences of prejudice that triggered their hopelessness. Second, many participants perceived their HIV as a personal failure and felt shamed and blamed, heightening men's suicidality. Third, to avoid disgrace, men withdrew from social interactions, resulting in isolation. However, the subsequent dearth of social interaction weighed heavily, as men admitted longing for social, sexual and romantic connections. All themes contributed in complex ways to participants' experiences of suicidality. The findings affirm the need for tailored suicide prevention efforts focused on promoting social connectedness and public health efforts to de-stigmatize HIV and mental illness.